2007
DOI: 10.1007/s11284-007-0432-6
|View full text |Cite
|
Sign up to set email alerts
|

How do dams affect freshwater fish distributions in Japan? Statistical analysis of native and nonnative species with various life histories

Abstract: We examined the effects of dams on freshwater fish species based on data collected during 1990-2004 from 200 drainage systems in Japan. Of the 76 fish species examined, the occurrence of 20 species within Petromyzontidae, Cyprinidae, Cobitididae, Salmonidae, Cottidae, and Gobiidae was negatively affected by the presence of dams located in the downstream reaches of fish survey sites, whereas the occurrence of 12 species within Cyprinidae, Adrianichthyidae, Centrarchidae, and Gobiidae was positively associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 40 publications
(44 reference statements)
1
53
0
Order By: Relevance
“…Spatial distribution shows some discipline and is closely related to the needs of any living being's growth and survival. Documentation of the impact of dams on freshwater fish distribution in Japan revealed that habitat fragmentation was the main factor that affected species distribution [36]. In this study, impoundment changed the algal spatial distribution regime and altered the status of algal cell gathering in the surface water.…”
Section: ) Effects Of the Impoundment On The Phytoplankton Communitymentioning
confidence: 70%
“…Spatial distribution shows some discipline and is closely related to the needs of any living being's growth and survival. Documentation of the impact of dams on freshwater fish distribution in Japan revealed that habitat fragmentation was the main factor that affected species distribution [36]. In this study, impoundment changed the algal spatial distribution regime and altered the status of algal cell gathering in the surface water.…”
Section: ) Effects Of the Impoundment On The Phytoplankton Communitymentioning
confidence: 70%
“…there was no river fragmentation or flow regulation, the OP of 28 fish species would increase further compared to the increase in scenario D2, while only two fish species that had higher occurrence probabilities in D2 than D1 would decrease. As mentioned above, river fragmentation limits the migration of diadromous fish and decreases their OP (Fukushima et al 2007, Han et al 2008. Furthermore, the indirect effects of dams, e.g.…”
Section: The Effects Of Flow Regulation and Fragmentation On Fish Opmentioning
confidence: 96%
“…The proportion of Coreius in the catch declined to 54% from ~80% ( Figure 2). Because of the habitat selectivity of different species [44,45], significant changes in species compositions resulted in the spatial variability of fish distribution ( Figure 6). …”
Section: Variations In the Fish Assemblagesmentioning
confidence: 99%